Drug Resistant Epilepsy Among Patients Attended The Neurosciences Hospital - Zaer, Nael Husain (AL-Kindy College Medical Journal, 2019)
Background: Drug resistant epilepsy is defined as failure of adequate trials of two tolerated, appropriately chosen and used antiepileptic drug schedules to achieve sustained seizure freedom. Up to 30% of patients referred to clinics with a diagnosis of pharmaco-resistant epilepsy may have been misdiagnosed, and many can be helped by optimizing their treatment.Pseudoresistance, in which seizures persist because the underlying disorder has not been adequately or appropriately treated, must be ruled out or corrected before drug treatment can be considered to have failed. Objectives: The objectives of this study were to determine the causes of drug failure in patients with epilepsy and to differentiate between drug resistant epilepsy and pseudoresistant epilepsy. Type of the study: This is a retrospective study. Method: It is conducted in Baghdad governorate at the epilepsy clinic in the neurosciences hospital during the period from the 1st of February through July 2013. Two hundred patients with refractory epilepsy were involved. These patients attended the epilepsy clinic during 2011 and 2012. The data was collected from the files of the patients including age, gender, weight, history of presenting illness, type of seizure, drugs used, duration of disease, EEG and imaging findings, compliance and follow up. Results: Drug resistance epilepsy constituted a prevalence of 24% (128) as the total number of patients with epilepsy attending the hospital during the same period was 527.The mean age of patients with refractory epilepsy was 25 years. Male were 56.5% (113/200) and urban residents were 70.5% (141/200). The study revealed that 64% (128/200) of refractory epilepsy was attributed to drug resistance; while the remaining proportion was pseudoresistance 36% (72/200). The main cause of pseudoresistance was poor compliance 36.1% (26/72).The most common type of seizure in the sampled patients was generalized tonic clonic seizures in 51.5% (103/200).Compliance was found to be statistically associated with abnormal EEG finding, past medical history (hypertension, cardiac diseases, encephalitis, diabetes mellitus and any significant history) and quality of follow up. The follow-up was found to be statistically associated with the family history, past medical history( encephalitis and hypertension) and compliance of patient. Conclusion:A considerable number of patientsdiagnosed as cases of drug resistant epilepsy had another explanation causing drug failure.The study recommends the application of consensus definition for drug resistant epilepsy and periodic evaluation of patients with drug resistant epilepsy to exclude pseudoresistance.